(untitled) - Schofield, James (Thành phố Hồ Chí Minh, 2012)
This series of podcasts helps you to improve your English for your career in the workplace and covers a large number of business and work themes. They are suitable for learners at intermediate to advanced level.
Keywords: English language,Tiếng Anh; Textbooks for foreign speakers,Giáo trình cho người nói tiếng nước ngoài